Sustainable Capture Fisheries Optimization for Blue Economy and Fishermen’s Welfare in Indonesia - Tambun, Robert; Sutrisno, Sutrisno; Prasutiyon, Hadi (Departemen Teknik Kelautan Universitas Hasanuddin, 2025)
The largest fish potential in Indonesian waters is in the waters covering the Aru Sea, Arafuru Sea and Eastern Timor Sea. This is based on data from the Directorate General of Capture Fisheries of the Ministry of Maritime Affairs and Fisheries (January 2018), the potential fishery capability is 2,637,565 tons. With this potential, the amount that can be developed and utilized to be caught is 2,110,053 tons. This catch limit is a signal to continue to maintain fish stocks in these waters. In addition to this, these waters also have the most ship permit allocations with the number of ship permits granted by KKP totaling 1,368. Meanwhile, in the territory of the Republic of Indonesia, the lowest potential fisheries are in the waters of the Strait of Malacca and the Andaman Sea, whose potential fisheries are 425,444 tons. However, 340,355 tons can be caught.